Lenalidomide plus dexamethasone is more effective than dexamethasone alone in patients with relapsed or refractory multiple myeloma regardless of prior thalidomide exposure - Wang, M.; Dimopoulos, M.A.; Chen, C.; Cibeira, M.T.; Attal, M.; Spencer, A.; Rajkumar, S.V.; Yu, Z.; Olesnyckyj, M.; Zeldis, J.B.; Knight, R.D.; Weber, D.M. (Blood, 2008)
This analysis assessed the efficacy and safety of lenalidomide + dexamethasone in patients with relapsed or refractory multiple myeloma (MM) previously treated with thalidomide. Of 704 patients, 39% were thalidomide exposed. Thalidomide-exposed patients had more prior lines of therapy and longer duration of myeloma than thalidomide-naive patients. Lenalidomide + dexamethasone led to higher overall response rate (ORR), longer time to progression (TTP), and progression-free survival (PFS) versus placebo + dexamethasone despite prior thalidomide exposure. Among lenalidomide + dexamethasone-treated patients, ORR was higher in thalidomide-naive versus thalidomide-exposed patients (P = .04), with longer median TTP (P = .04) and PFS (P = .02). Likewise for dexamethasone alone-treated patients (P = .03 for ORR, P = .03 for TTP, P = .06 for PFS). Prior thalidomide did not affect survival in lenalidomide + dexamethasone-treated patients (36.1 vs 33.3 months, P > .05). Thalidomide-naive and thalidomide-exposed patients had similar toxicities. Lenalidomide + dexamethasone resulted in higher rates of venous thromboembolism, myelosuppression, and infections versus placebo + dexamethasone, independent of prior thalidomide exposure. Lenalidomide + dexamethasone was superior to placebo + dexamethasone, independent of prior thalidomide exposure. Although prior thalidomide may have contributed to inferior TTP and PFS compared with thalidomide-naive patients, these parameters remained superior compared with placebo + dexamethasone; similar benefits compared with placebo + dexamethasone were not evident for thalidomide-exposed patients in terms of overall survival. Studies were registered at http://www.clinicaltrials. gov under NCT00056160 and NCT00424047. © 2008 by The American Society of Hematology.